Implementasi Jaringan Internet Menggunakan Tenda N301 - Ardiansyah, Ardiansyah (Yayasan Kawanad, 2024)
This research examines the implementation of internet networks using Tenda N301 router in Pidie Regency as a connectivity solution for areas with infrastructure limitations. The research methodology employs a qualitative approach with descriptive analysis conducted at three strategic locations: Peutoe Village Office, SDN 1 Sigli, and Sigli Public Health Center during the period from July to December 2019. Implementation was carried out through stages of site survey, device installation and configuration, network performance measurement, load testing, and 30-day monitoring to evaluate system reliability and performance. Research results demonstrate satisfactory technical performance with average download speed of 28.8 Mbps, upload speed of 11.6 Mbps, latency of 15.2 ms, and packet loss of 0.2%. Effective coverage area reaches an average of 1,978 m² with capability to handle 18-20 concurrent users. User satisfaction level reaches a score of 4.2 out of 5.0 with 99.1% uptime during the monitoring period. Security implementation using WPA2-PSK, guest network, and MAC address filtering provides adequate protection for public institutional environments. Economic analysis shows positive return on investment within 8-12 months with low total cost of ownership. This research proves that entry-level routers such as Tenda N301 can be an effective and efficient solution for improving internet connectivity in remote areas, despite having limitations in user capacity and coverage area. The implementation model developed can serve as a template for similar deployments in other areas with similar geographical and socio-economic characteristics.